Semantic based navigation and lane keeping - Abdeen, Abdallah Adel (2023)
A Master of Science thesis in Mechatronics Engineering by Abdallah Adel Abdeen entitled, “Semantic based navigation and lane keeping”, submitted in April 2023. Thesis advisor is Dr. Shayok Mukhopadhyay. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).